Roux-en-Y gastric bypass-induced perturbative changes in microbial communities and metabolic pathways in rats - Yang, Jing; Chen, Lei; Shang, Xue-Ying; Chen, Yi-Lin; Zhao, Shan-Shan; Jin, Shi; Yang, Jing; Liu, Hui-Xin; Du, Jian (Frontiers in Microbiology, 2022)
Background Obesity has become a global health and socioeconomic problem because of an inadequate balance between energy intake and energy expenditure. Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) are the two most commonly used strategies for weight loss, which have been proven to benefit from gut microbiota restoration. Methods Rats received SG, RYGB, and sham operations for 10 weeks. At the end of the experiment, the fecal microbiota was analyzed using 16s rRNA gene sequencing. In addition, the shift in the plasma metabolism of rats that underwent RYGB surgery was analyzed using untargeted metabolomics. The crosstalk between microbiome and metabolites was revealed using metabolic pathway enrichment and integrated analysis. Result The SG surgery induced a modest shift in the gut microbiota relative to the RYGB. RYGB significantly decreased the alpha diversity and Firmicutes/Bacteroides (F/B) ratio and increased the proportion of Escherichia, Bacteroides, and Akkermansia genera compared to sham and SG operations. The predicted function of gut microbiota revealed that the RYGB surgery uniquely enhanced the capability of linoleic acid and sphingolipid metabolism. Furthermore, the circulating serine, phosphatidylcholine (PC) 20:5/22:5, riboflavin, L–carnitine, and linoleic acid were evaluated after RYGB surgery. In addition, the metabolic pathway enrichment and integrated analysis suggest that the RYGB induced Escherichia, Bacteroides, and Akkermansia might inhibit the sphingonine and phytosphingosine metabolisms from serine and promote the PC (20:5/22:5) metabolism to produce linoleic acid. Conclusion This comprehensive analysis not only revealed the difference in the gut microbiota shifts after SG and RYGB but also discovered the perturbative changes in microbial communities and metabolic pathways after RYGB surgery, which provided clues for improving the beneficial effect of RYGB in metabolic disease intervention via regulating bacterial-metabolite crosstalk.